PENINGKATAN KUALITAS PRODUKSI PELAT DINDING DAN ATAP INSULATED PANEL SYSTEM PENERAPAN METODE SIX SIGMA DENGAN KONSEP DMAIC - Ridwan Usman (Universitas Ahmad Dahlan Indonesia, 2019)
This research aims to identify, measure, and analyze process production of EPS (Expanded Polystyrene) Sandwich Panel produced by PT. BI. It also gave recommendation to improve the process production for increasing product quality. This products produced by PT. BI is still have high defects so that it need improvementÂ to decrease defect product. The approach used to solve this problem is Six Sigma method based on the stages of DMAIC (Define, Measure, Analyze, Improve and Control). Identification for defect product consists of defects occurred in the process bending plate, gluing, press roll pressing and cutting. The results of previous research obtained DPMO (Defect Per Million Opportunities) value is 6500 and sigma level is 3.98. It has not reached the expected target of 6 sigma. Analysis using fishbone diagram and FMEA (Failure Mode and Effect Analysis) show that there is need for corrective action to improve company's performance. Proposed quality improvement is conducted by installing plastic roll (laminating coating) and replacing broken roll press. The result of proposed improvement shows DPMO value is 3227 and the sigma level is 4.22.